Breaking the biofilm barrier: The role of stabilizers in biofilm penetration and pulmonary antibiotic delivery by polymer nanoparticles - Ernst, Julia; Klinger-Strobel, Mareike; Thamm, Jana; Makarewicz, Oliwia; Pletz, Mathias W.; Fischer, Dagmar (Pharmazeutische Industrie, 2019)
In infectious lung diseases, poly(lactide-co-glycolide) (PLGA) nanoparticles are highly advancing for drug delivery in respiratory tract infections due to their ability to overcome biological barriers such as bacterial lung biofilms and human mucus. As the selection of stabilizers used during the formulation of nanoparticles affects their surface properties, this study aimed to test different polymers for their capability to stabilize PLGA particles and their influence on biofilm and mucus penetration. Polyvinyl alcohol (PVA), chitosan (Cs), poloxamer 188 (P188), and poly(ethylene glycol) (PEG) were selected to prepare fluorescently labeled spherical nanoparticles of 550-800 nm using an emulsion-diffusion-evaporation technique. In an artificial mucus system particle permeation was found to increase depending on particle size and stabilizer type with P188 < PVA < PEG < Cs. In vitro penetration of biofilms of Burkholderia cepacia and Staphylococcus aureus gave comparable results. The covalent binding of PEG to PLGA improved the penetration ability in all assays and as proof of concept demonstrated the highly efficient bacterial killing of biofilm-embedded B. cepacia after tobramycin encapsulation compared to free drug.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biofilm; Burkholderia cepacia; Nanoparticle; Stabilizer; Staphylococcus aureus; Tobramycin